2007
DOI: 10.1128/aem.02736-06
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Diversity of Coastal Vibrio cholerae Strains Is Linked to Environmental Factors

Abstract: Studies of Vibrio cholerae diversity have focused primarily on pathogenic isolates of the O1 and O139 serotypes. However, autochthonous environmental isolates of this species routinely display more extensive genetic diversity than the primarily clonal pathogenic strains. In this study, genomic and metabolic profiles of 41 non-O1/O139 environmental isolates from central California coastal waters and four clinical strains are used to characterize the core genome and metabolome of V. cholerae. Comparative genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 40 publications
11
65
0
Order By: Relevance
“…Modifications of cellular morphology should be related to modifications with carbohydrates metabolites contained in pariatal membranes for these species. Keymer et al (2007) described similar results for V.cholerae and pointed that environmental parameters, measured in situ during sample collection, should correlated to the presence of specific dispensable genes and metabolic capabilities, including utilization of mannose, sialic acid, citrate, and chitosan oligosaccharides. Thus, gene content identified and metabolic pathways that are likely selected for in certain coastal environments and may influence V. cholerae population structure in aquatic environments.…”
Section: In Vitro Starvation Effect On Catabolic Carbohydrates Profilsupporting
confidence: 49%
“…Modifications of cellular morphology should be related to modifications with carbohydrates metabolites contained in pariatal membranes for these species. Keymer et al (2007) described similar results for V.cholerae and pointed that environmental parameters, measured in situ during sample collection, should correlated to the presence of specific dispensable genes and metabolic capabilities, including utilization of mannose, sialic acid, citrate, and chitosan oligosaccharides. Thus, gene content identified and metabolic pathways that are likely selected for in certain coastal environments and may influence V. cholerae population structure in aquatic environments.…”
Section: In Vitro Starvation Effect On Catabolic Carbohydrates Profilsupporting
confidence: 49%
“…In particular, traits associated with the assimilation of small organic carbon sources are highly phylogenetically dispersed. This result is consistent with observations of wide variation among the strains of E.coli, Acinetobacter, Vibrio, etc., in their ability to use particular carbon substrates (Sarma et al, 2004;Keymer et al, 2007;Vieira et al, 2011). Previous studies have identified other phylogenetically dispersed bacterial traits like nutrient acquisition (Martiny et al, 2006) and particle colonization (Hunt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and characterization of the California Vibrio cholerae strains used here are described in the report by Keymer et al (27). O1 (N16961 [25], VCX-B21 [31], A1552 [60], O395 [53]) and O139 (MO3 [41]) reference strains have been described previously.…”
Section: Methodsmentioning
confidence: 99%